Association between dietary inflammatory index and all-cause mortality in patients with osteoporosis: data from NHANES - Fan, Teng-di; Bei, Di-kai; Li, Song-wei (Frontiers in Nutrition, 2025)
BackgroundOsteoporosis is a common bone metabolic disease that poses a serious risk of fracture and death. The dietary inflammatory index (DII) is a tool for assessing the impact of diet on the inflammatory response in the body. This study aims to investigate the association of DII with the all-cause mortality of those patients.MethodsThe study population was screened from the National Health and Nutrition Examination Survey (NHANES), after applying the exclusion criteria of age <18 years or missing information on DII, femoral bone marrow density (BMD), age, sex, ethnicity, and other variables. The DII was calculated according to the questionnaire interview of 24-h dietary data. Data analysis methods included the t-test, chi-squared test, weighted Cox regression, Kaplan–Meier (KM) survival analysis, XGBoost analysis, Pearson’s analysis, and interaction analysis.ResultsA total of 361 patients were included in the study, comprising 264 women and 97 men. The Cox regression analysis results indicated that DII, glycohemoglobin, BMI, weight, age, race, and diabetes were independent factors for all-cause mortality (all p < 0.05). In addition, patients with higher DII levels had a higher risk of all-cause mortality than those with lower DII (p < 0.05). The KM survival curves indicated that patients with lower DII levels had a longer survival time (p < 0.05). The variable importance ranking, including DII and other variables, was as follows: age, weight, BMI, glycohemoglobin, DII, ethnicity, and diabetes. Pearson’s correlation analysis further indicated that DII was not significantly correlated with any of them.ConclusionLower DII is independently associated with longer survival time in patients with osteoporosis.